MICROSATELLITE HYBRID STRUCTURE USING ALUMINUM 7075-T6 AND CFRP FOR IMPROVED LAUNCH PERFORMANCE SURVIVABILITY - Thuy Linh, Nguyen; Cong Thai, Nguyen; Xuan Huy, Le; Anh Duc, To (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This study presents the structural design and simulation of a 50 kg-class microsatellite developed for compatibility with the JAXA Epsilon launch vehicle. A hybrid architecture combining Aluminum 7075-T6 and Carbon Fiber Reinforced Polymer (CFRP) was employed to meet stringent mass, stiffness, and vibration requirements. The final structure, measuring 480 × 488 × 550 mm, achieved a total mass of 45 kg, falling within the required launch envelope. Finite element simulations were conducted using ANSYS 2024R2 to evaluate modal, sine-sweep, random vibration, and shock responses under launch-induced conditions. The first three natural frequencies, 118.99 Hz (X-axis), 123.77 Hz (Y-axis), and 240.42 Hz (Z-axis), surpassed the required thresholds, avoiding resonance with vehicle-induced excitations. Vibration analyses confirmed that peak acceleration responses remained within safe operational margins, with sine-sweep, random vibration, and shock responses showing no modal amplification. Component-level stress simulations revealed von Mises stress values well below material limits across all critical subsystems. These results validate the structural integrity and dynamic survivability of the hybrid microsatellite, demonstrating its readiness for spaceflight.